2020
DOI: 10.2196/preprints.19896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting Engagement in Web-Based Health Care Patient Information: Narrative Review of the Literature (Preprint)

Abstract: BACKGROUND The online world is rapidly becoming the primary source of healthcare information. There is a pressing need for online healthcare content not only to be accurate but also engaging. Improved engagement of people with online healthcare content has the potential to inform but also to influence behavioural change to make healthier choices. Factors associated with better engagement with online healthcare content have previously not been well considered. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…A systematic review evaluating factors associated with engaging web-based content revealed the following key categories: textual information, discussion boards and web-based groups, video content, visual or pictographs, device accessibility, stage of patient journey, credibility, and completeness of information [ 57 ]. A framework was developed for each category describing the factors that should be considered when designing an effective content.…”
Section: Content Personalizationmentioning
confidence: 99%
“…A systematic review evaluating factors associated with engaging web-based content revealed the following key categories: textual information, discussion boards and web-based groups, video content, visual or pictographs, device accessibility, stage of patient journey, credibility, and completeness of information [ 57 ]. A framework was developed for each category describing the factors that should be considered when designing an effective content.…”
Section: Content Personalizationmentioning
confidence: 99%